2020
DOI: 10.3390/ijms21072361
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Affects Dopamine Metabolism and Causes Changes in the Expression of Dopamine Receptors (D1R and D2R) in Chosen Brain Structures of Morphine-Dependent Rats

Abstract: Disturbances caused by excess or shortages of certain elements can affect the cerebral reward system and may therefore modulate the processes associated with the development of dependence as was confirmed by behavioural studies on animals addicted to morphine. Earlier publications demonstrated and proved the neurodegenerative properties of both low and high doses of fluoride ions in animal experiments and in epidemiological and clinical studies. The aim of the experiments conducted in the course of the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Previous studies have demonstrated that fluoride has an impact on morphine dependence and tolerance by influencing the levels and metabolism of dopamine in structures associated with dependence, as well as serotonin and norepinephrine in the hippocampus and neocortex. Additionally, it can modulate the expression of receptors for these monoamines [45,46]. This evidence highlights the potential of fluoride, as an environmental factor, to affect the state of dependence.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Previous studies have demonstrated that fluoride has an impact on morphine dependence and tolerance by influencing the levels and metabolism of dopamine in structures associated with dependence, as well as serotonin and norepinephrine in the hippocampus and neocortex. Additionally, it can modulate the expression of receptors for these monoamines [45,46]. This evidence highlights the potential of fluoride, as an environmental factor, to affect the state of dependence.…”
Section: Discussionmentioning
confidence: 73%
“…Our analysis suggests that fluoride pre-exposure influences the response to morphine administration in the hippocampus. Previous studies have shown that in rats perinatally treated with fluoride, morphine can decrease the expression of D1 and D2 receptors, as well as dopamine concentration in the hippocampus [45]. The impulses originating from hippocampal areas may stimulate the mesolimbic pathway [3,49], which is crucial in the initiation and development of dependence [3].…”
Section: Cox-1 Dependent Inflammatory Response In Morphine Dependence...mentioning
confidence: 99%
“…Fluoride may be significantly dangerous to the human nervous system and have been known to penetrate the blood-brain barrier, where, through generation of free radicals, oxidative stress conditions are promoted, causing impaired function of myelin, neurons and neurotransmitters, associated with lower IQ scores, depression, disturbances in learning processes and psychomotor skills [7,[23][24][25]. Several studies have reported that fluoride can be toxic to the reproductive system causing decreased fertility [26,27] Recently, reports have indicated fluoride toxicity during immune and inflammatory responses and impaired glucose tolerance with insulin resistance in peripheral tissues [7].…”
Section: Discussionmentioning
confidence: 99%
“…Fluoride causes degenerative changes in all parts of the brain and in the spinal cord, including axon deterioration, myelin sheath degeneration, mitochondrial damage, and alterations in synaptic ultrastructure [ 56 , 60 ]. It also affects neurotransmitter metabolism and causes changes in the expression of neurotransmitter receptors [ 61 , 62 , 63 ]. Fluorine compounds impair energy metabolism of the brain, dependent primarily on the burning of glucose.…”
Section: Fluoride As An Environmental Toxinmentioning
confidence: 99%